2015
DOI: 10.15330/jpnu.2.1.38-50
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Copper-Containing Pesticides: Metabolism, Toxicity and Oxidative Stress

Abstract: Abstract. The purpose of this paper is to provide a brief review of the current knowledge regarding metabolism and toxicity of copper and copper-based pesticides in living organisms. Copper is an essential trace element in all living organisms (bacteria, fungi, plants, and animals), because it participates in different metabolic processes and maintain functions of organisms. The transport and metabolism of copper in living organisms is currently the subject of many studies. Copper is absorbed, transported, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 65 publications
0
48
0
3
Order By: Relevance
“…For example, pesticide poisoning accompanied by acute liver intoxication has been associated with chronic pesticide exposure (Hodgson and Goldstein, 2001[ 74 ]). Kidney is a secondary organ involved in detoxification related to big extent by its high blood flow and its ability to concentrate and convert pesticides due to which it is a target for xenobiotic toxicity (Husak et al, 2014[ 79 ], 2017[ 80 ]; Husak, 2015[ 78 ]). Very little is known about xenobiotic detoxification in the central nervous system although several studies have demonstrated efficient relationships between development of neurotoxicity and exposure to organophosphorus compounds (Galloway and Handy, 2003[ 57 ]; Vani et al, 2011[ 181 ]).…”
Section: Persistent Status Of Pesticides In the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, pesticide poisoning accompanied by acute liver intoxication has been associated with chronic pesticide exposure (Hodgson and Goldstein, 2001[ 74 ]). Kidney is a secondary organ involved in detoxification related to big extent by its high blood flow and its ability to concentrate and convert pesticides due to which it is a target for xenobiotic toxicity (Husak et al, 2014[ 79 ], 2017[ 80 ]; Husak, 2015[ 78 ]). Very little is known about xenobiotic detoxification in the central nervous system although several studies have demonstrated efficient relationships between development of neurotoxicity and exposure to organophosphorus compounds (Galloway and Handy, 2003[ 57 ]; Vani et al, 2011[ 181 ]).…”
Section: Persistent Status Of Pesticides In the Environmentmentioning
confidence: 99%
“…Jegerschöld et al (1995[ 85 ]) demonstrated that copper ions blocked the electron donation from Tyrz to P680 (Figure 4 (Fig. 4) ; Reference in Figure 4: Husak, 2015[ 78 ]). Moreoever, the central magnesium atom of chlorophyll was found to be substituted by ions of mercury, copper, or cadmium, inhibiting in this manner operation of photosystem (Küpper et al, 1996[ 96 ]).…”
Section: Classification Of Pesticides: General Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…are the toxic effects of copper (Adrees et al, 2015). Being very high status of available copper in the soil, care should have to take during fungicide, pesticides, herbicides application in the field because these chemical already contains copper element (Husak, 2015). Available copper showed moderate variability (48.64%) among the soil samples.…”
Section: Available Coppermentioning
confidence: 99%
“…Copper is a micronutrient essential for life; copper follows a specific homeostatic regulation mechanism, which allows excess copper to be excreted mainly through the bile. Copper is absorbed, transported, distributed, stored, and excreted in the body according to complex homeostatic processes which ensure a constant and sufficient supply of the micronutrient while simultaneously avoiding excess levels (Husak 2015). Target organs of excess copper after oral administration are the liver and the kidneys.…”
Section: Introductionmentioning
confidence: 99%